2024
DOI: 10.1248/cpb.c23-00811
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activities of Cynaropicrin and Related Compounds against Cancer Stem Cells

Kousuke Araki,
Minami Hara,
Shohei Hamada
et al.

Abstract: Glioblastoma (GBM) has a high mortality rate despite the availability of various cancer treatment options. Although cancer stem cells (CSCs) have been associated with poor prognosis and metastasis, and play an important role in the resistance to existing anticancer drugs and radiation; no CSC-targeting drugs are currently approved in clinical practice. Therefore, the development of antiproliferative agents against CSCs is urgently required. In this study, we evaluated the antiproliferative activities of 21 ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported the effectiveness of compounds possessing a carbonyl motif in GB management. For instance, the α,β-unsaturated carbonyl moiety of guaianolide sesquiterpene lactone cynaropicrin (1) expressed strong antiproliferative activity within U251MG glioblastoma cancer stem cells, suggesting potential therapeutic applications in targeting GB . In addition, a different sesquiterpene compound, compound 12 (oxyphyllanene B, OLB), which also possess an α,β-unsaturated carbonyl moiety was observed to induce apoptosis in time- and dose-dependent manners within TMZ-resistant GB cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the effectiveness of compounds possessing a carbonyl motif in GB management. For instance, the α,β-unsaturated carbonyl moiety of guaianolide sesquiterpene lactone cynaropicrin (1) expressed strong antiproliferative activity within U251MG glioblastoma cancer stem cells, suggesting potential therapeutic applications in targeting GB . In addition, a different sesquiterpene compound, compound 12 (oxyphyllanene B, OLB), which also possess an α,β-unsaturated carbonyl moiety was observed to induce apoptosis in time- and dose-dependent manners within TMZ-resistant GB cells …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the α,β-unsaturated carbonyl moiety of guaianolide sesquiterpene lactone cynaropicrin (1) expressed strong antiproliferative activity within U251MG glioblastoma cancer stem cells, suggesting potential therapeutic applications in targeting GB. 11 In addition, a different sesquiterpene compound, compound 12 (oxyphyllanene B, OLB), which also possess an α,β-unsaturated carbonyl moiety was observed to induce apoptosis in time-and dose-dependent manners within TMZ-resistant GB cells. 12 In the current study, we sought to investigate the efficacy of an in-house synthesized β-AC compound, b3-(4-bromophenyl)-1-phenyl-3-(phenylamino)propan-1-one (SHG-8), and its effects upon miRNA regulation within GB cell models.…”
Section: Introductionmentioning
confidence: 99%